Violence and bordering on the margins of the State: A view from South Africa and the southern border of Spain - Super, Gail (Theoretical criminology, 2022)
This article examines expulsions in and around the Spanish enclaves of Ceuta and Melilla and in informal settlements in former black townships in South Africa. These violent bordering processes expose the violent injustices that constitute the boundaries of lawful (liberal) law, and the violence that sovereigns use to secure territories. Drawing on Walter Benjamin we make three main theoretical arguments. First, that the bordering processes in our case studies are instances of law (and State) preserving violence. Second, that absence and responsibilization are central techniques for invisibilizing the role of violence in preserving law, and that abdication of jurisdiction is key to the exercise of state sovereignty. Third, that when the State preserves itself through sharing its monopoly over violence the fictitious distinction between law and violence collapses. We use the term ‘borderline lawful violence’ to highlight the precarious nature of the boundary between lawful and unlawful violence.